Persepsi siswa terhadap penggunaan digital storytelling sebagai media dalam pengajaran berbicara bahasa Inggris di Anuban Chumchon Phukradueng School - Siti Mazuroh Asmawati; Candra Hadi Asmara (DIDAKTIKA, 2023)
This study aimed to investigate the students’ perception on the use of digital storytelling as a media in learning to speak English at 3rd grade students at Anuban Chumchon Phukradueng School, one of the junior high schools in Loei, Thailand. The method used in this study is a qualitative method. A descriptive qualitative design was employed as a research design in this study. The subject of this study was 35 students. The instrument used in this study was adapted questionnaire and interview from the other researcher. According to the findings of this study, using digital storytelling can help students developed their speaking abilities. It could be seen from the result of questionnaire, most of students find digital storytelling help them in improving their speaking skills. Furthermore, students gave positive responses during interviews. Digital storytelling is an engaging and enjoyable method for students studying English. Because as a media, digital storytelling provide video that contain combination of pictures, animation, text and sound to convey story to the audience. The students find it easy to understand the lesson by using digital storytelling.